The long-term results of the impact of rhinophototherapy on quality of life in cases with allergic rhinitis - Yaz, Aytekin; Cingi, Cemal; Kezban Gürbüz, Melek; Bal, Cengiz (ENT Updates, 2012)
Objective: In this study the effects of intranasal rhinophototherapy on symptoms of allergic rhinitis, physical examination findings, and quality of life of our patients with allergic rhinitis have been investigated. Methods: Our study group consisted of the patients followed up for at least 2 years with diagnosis of allergic rhinitis in our outpatient clinic. Among them the first 100 patients who underwent nasal phototherapy from January 2006 on, and followed up by us at least one year constituted our study group. The patients presenting with complaints of rhinorrhea, nasal itching, and stuffiness had undergone all physical examinations of Ear Nose and Throat system. Specific IgE levels were determined, and skin Prick tests were performed. Results: Our study group consisted of 32 male and 69 female patients with a median age of 35.09 (range 18 to 52) years. When the responses to "The Rhinoconjunctivitis Quality of Life Questionnaire" for adults were evaluated globally, it can be concluded that phototherapy method applied had improved quality of life markedly at the end of one month, but the level of improvement did not remain the same up to 3rd months, on the contrary it decreased, and at end of one year it attenuated significantly. In the short-term the most apparent response to phototherapy was observed in nasal symptoms, restricted activities, and sleep parameters. However, ocular and non-allergic symptoms improved minimally. Conclusion: As an outcome of our study, it was detected that phototherapy improved symptoms of allergic rhinitis, and physical examination findings, and effected quality of life scores favorably. However in the long run, it was concluded that adequate responses could not be obtained.